1999
DOI: 10.1093/ndt/14.11.2726
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of arteriovenous fistulas complicating percutaneous renal biopsy in three paediatric cases

Abstract: The technique of superselective embolization using a coaxial catheter is an effective and safe method in the treatment of post-biopsy AVFs and pseudoaneurysm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
3
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 10 publications
1
35
3
2
Order By: Relevance
“…Total nephrectomy would likely have been necessary if the embolization had failed; this would be particularly undesirable in a patient with Alport syndrome, in whom the loss would hasten or increase the risk of future end-stage renal disease (ESRD). In the pediatric population, bucrylate, lipiodol, and coils have been utilized for embolization of renal AVFs [13]. The Amplatzer vascular plug has been used for occlusion of renal AVF in an adult patient [14].…”
Section: Discussionmentioning
confidence: 99%
“…Total nephrectomy would likely have been necessary if the embolization had failed; this would be particularly undesirable in a patient with Alport syndrome, in whom the loss would hasten or increase the risk of future end-stage renal disease (ESRD). In the pediatric population, bucrylate, lipiodol, and coils have been utilized for embolization of renal AVFs [13]. The Amplatzer vascular plug has been used for occlusion of renal AVF in an adult patient [14].…”
Section: Discussionmentioning
confidence: 99%
“…2,3,7 Bilge et al 11 reported that none of their 3 cases of symptomatic AVFs that occurred after renal biopsy resolved spontaneously; rather, they caused life-threatening bleeding. Alcazar et al 8 reported a case without radiologic follow-up who suffered from late development of hypertension and high-output cardiac failure, in which an AVF was detected via renal Doppler sonography 25 years after a renal biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Transarterial embolization is an effective technique that can safely be used in major renal vascular injuries [2,[6][7][8][9]. It replaces emergency surgery, which is the only alternative in a patient with lifethreatening hematuria [2,10].…”
Section: Discussionmentioning
confidence: 99%
“…Injury to the intrarenal arterial system can cause an arteriovenous fistula and/or pseudoaneurysm [1][2][3][4][5]. Endovascular embolization is accepted as the recommended treatment of these lesions [2,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation